A novel control circuit for piezoelectric energy harvesting. (July 2021) - Zhang, Zhang; Zechen, Tang; Yunfeng, Zhang; Xin, Cheng; Guangjun, Xie
Abstract: A novel piezoelectric energy harvesting circuit is proposed. This circuit consists of a piezoelectric element, synchronized switch harvesting on capacitors (SSHC) circuit, two sampling resistors, control circuit, full-bridge rectifier, and load. The control circuit is composed of a zero-crossing detection circuit and a pulse generation circuit. The zero-crossing detection circuit adopts sampling resistance method, which is more accurate and easier to implement than the traditional voltage comparison method. The control signal for controlling switches in the SSHC circuit is generated by pulse generation circuit and its width is dynamically adjusted according to the state of the flipping process. Compared with circuit that uses capacitors to control the width of the control signal, this circuit is easier to implement and has a higher output efficiency. Experiment results show that the circuit proposed can accurately detect the zero-crossing time and automatically adjust the pulse width of the control signal according to the state of the circuit. The output power of the proposed circuit is 1.80 ​mW with 10 ​kΩ load resistance, which is four times that of the traditional SSHC circuit.